Extraction of enhanced, ultrashort laser pulses from a passive 10-MHz stack-and-dump cavity - Breitkopf, Sven; Wunderlich, Stefano; Eidam, Tino; Shestaev, Evgeny; Holzberger, Simon; Gottschall, Thomas; Carstens, Henning; Tünnermann, Andreas; Pupeza, Ioachim; Limpert, Jens (Springer International Publishing, 2018)
Periodic dumping of ultrashort laser pulses from a passive multi-MHz repetition-rate enhancement cavity is a promising route towards multi-kHz repetition- rate pulses with Joule-level energies at an unparalleled average power. Here, we demonstrate this so-called stack-and-dump scheme with a 30-m-long cavity. Using an acousto-optic modulator, we extract pulses of 0.16 mJ at 30-kHz repetition rate, corresponding to 65 stacked input pulses, representing an improvement in three orders of magnitude over previously extracted pulse energies. The ten times longer cavity affords three essential benefits over former approaches. First, the time between subsequent pulses is increased to 100 ns, relaxing the requirements on the switch. Second, it allows for the stacking of strongly stretched pulses (here from 800 fs to 1.5 ns), thus mitigating nonlinear effects in the cavity optics. Third, the choice of a long cavity offers increased design flexibility with regard to thermal robustness, which will be crucial for future power scaling. The herein presented results constitute a necessary step towards stack-and-dump systems providing access to unprecedented laser parameter regimes.
CRIS-Team Scopus Importer:2023-04-20